Towards a good governance of pluralistic society in Malaysia: a study on the prospects and challenges for a successful Inter-Religious Dialogue (IRD) - Ibrahim, Haslina (2013)

(untitled)
The existence of various races, ethnic groups, and religions in Malaysia, maps the pluralistic condition of her society. Such co-existences however have exposed Malaysians to potential conflicts. In reality, conflicts did occur due to lack of understanding on each other’s religion. To reduce the conflicts, Inter-religious dialogue (IRD) has been propagated as an alternative in bridging religions in Malaysia. The issues at hands are; being a Muslim-majority state, what are needed by the Malaysian government to ensure the success of dialogue? Are Malaysians ready for such engagement? What are the prospects and challenges for a successful IRD in the Malaysian context? This paper therefore, aims to present a research findings pertaining to IRD. The findings are deemed necessary for mobilizing a good governance of pluralistic society in Malaysia.